Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/mot.0000000000000513
|View full text |Cite
|
Sign up to set email alerts
|

Obesity management in the liver transplant recipient

Abstract: Obesity-related liver disease has become one of the most common indications for liver transplantation and further research is needed to determine the role of bariatric surgery in the optimal management of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…If these dietary approaches are unwanted or ineffective, more aggressive techniques (such as bariatric surgery) can be considered for selected patients [ 122 ]. New approaches to weight loss using bariatric endoscopy are promising and need to be evaluated in transplant recipients [ 123 , 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…If these dietary approaches are unwanted or ineffective, more aggressive techniques (such as bariatric surgery) can be considered for selected patients [ 122 ]. New approaches to weight loss using bariatric endoscopy are promising and need to be evaluated in transplant recipients [ 123 , 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…95,96 Bariatric surgery in transplant patients has been comprehensively reviewed elsewhere. 97,98 Good outcomes have been reported with sleeve gastrectomy pre-and post-liver transplant, [99][100][101][102][103][104][105][106] as well as pre-and post-kidney transplant. 100,102,103 Combined liver transplant and sleeve gastrectomy also demonstrated improvement in weight and metabolic factors posttransplant.…”
Section: Nafld In Kidney Disease Patients and Morbid Obesitymentioning
confidence: 99%
“…In the setting of LT, the association with obesity has become more frequent, since obesity-related liver disease such as NAFLD/NASH is now one of three most common indications for listing for LT [120]. While some studies did not identify obesity as a predictor of poor prognosis, even when BMI was adjusted for ascites [15,121,122], others associated obesity with significantly lower post-LT survival, suggesting lower post-transplantation survival for obese LT recipient in comparing to a lean [123][124][125].…”
Section: Sleeve and Organ Transplantationmentioning
confidence: 99%
“…Despite higher morbimortality, BS appeared to be feasible and safe [129]. Likewise, a comprehensive review of the management of obesity in the LT settings has concluded that the optimal timing of bariatric surgery depends in part on the clinical condition of each patient [120]. Lastly, recent comprehensive review addressing the role of BS in the setting of organ transplantation has concluded that BS should be applied only after LT, and the SG is strongly recommended due to lower mortality, improvement on graft function, and preservation of easier endoscopic access to the biliary tree [112].…”
Section: Sleeve and Organ Transplantationmentioning
confidence: 99%